The Nigeria climate zones: Variability, trends and analysis from era-interim data (2010-2015) - Edokpa, David O; Ede, Precious N; Brown, Joshua; Adeyemi, Adewale J; Pukiche, Isaac U (International Journal of Climate Research, 2024)
This study analyses diurnal weather patterns in the lower atmosphere across four climate domains in Nigeria from Era-Interim data for synoptic hours of 0000, 0600, 1200 and 1800 hours from 2010-2015. The climate domain includes: Port Harcourt (tropical maritime), Enugu (bi-modal tropical continental), Jos (montane), Kano (mono-modal tropical continental) and Maiduguri (semi-arid). Findings revealed that air temperature across the areas indicate strong latitudinal positions with drier and hotter weather pattern northwards. Average air temperature across diurnal hours were 23.2-26oC, 23-29oC, 26-32oC, 26-34oC and 26.6-34 oC for Port Harcourt, Enugu, Jos, Kano and Maiduguri. Average solar radiation peaked at 1200 noon with values 508 W/m2, 639 W/m2, 830 W/m2, 905 W/m2, 832 W/m2 for the areas. Average wind speed increases northwards, i.e. 0.9-1.3m/s, 2.0-2.5m/s, 2.1-2.5m/s, 2.4-3.0m/s and 2.9-3.5m/s respectively. The wind variation is due to the surface characteristics across the areas. Southwesterly winds dominated coastal zone while southeasterly/northeasterly winds dominated the arid zone except during periods of peak rainy season. Average cloud cover for the coastal and northern domains in oktas was: 6-7 and 2-4. Relative humidity shows that prevailing atmospheric conditions at any given time are stronger at the areas close to the sources of influence and the position of Intertropical discontinuity (ITD). Humidity values were: 67-93% and 31-71% for coastal and northern domains. Rainfall amount reduces northwards i.e. 200-46 mm. Rainfall pattern is significantly influenced by the air masses source regions. These regions include closeness to massive water bodies, proximity to Sahara Desert and effects of mountainous barriers.